UI/UX Design for Point of Sale and Bookkeeping of Kasirmu Application (Case Study of MSMEs Actors in Cileunyi District, Bandung Regency) - Algiansyah, Muhamad Tri (Labkat Press KA FTIK UNIKOM, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are important in the Indonesian economy. Although they have a very large role in the Indonesian economy the failure rate of MSMEs is not low, especially in the first year of business. This study aims to analyze the challenges faced by MSMEs in financial management and to design application-based solutions to overcome these problems. The study was conducted in Cileunyi District, Bandung Regency, involving two MSME actors who have implemented digital bookkeeping. The results of the study indicate that the main obstacle for MSMEs lies in the discipline of financial recording, and separation of personal and business finances. To overcome these challenges, a mobile-based application was designed that integrates Point of Sale (POS) and bookkeeping features. The POS feature allows MSME actors to manage transactions, stock, and sales reports automatically. Providing an online ordering web menu, allows for an alternative POS for online purchases. The design of the user interface (UI/UX) adopts a Design Thinking approach to ensure that the application is by user needs and preferences. The results of the study show that the features contained in the Kasirmu application are to the needs of MSME actors in the Cileunyi District.